PENGARUH BENTUK PENILAIAN FORMATIF TERHADAP HASIL BELAJAR IPA SETELAH MENGONTROL PENGETAHUAN AWAL SISWA - Ismail, Muh Ilyas (Jurnal Biotek, 2015)
This research aims at identifying the effect of formative assessment type towards the learning achievement of Natural Sciences. This study applied 2 x 2 factorial design experimental methods. The population of the research is all the fift grade students of elementary school number 03 and 05 of Rawamangun Eastern Jakarta, with 80 students as sample, implementing inferential statistic assessment with ANCOVA. The study concludes (1) having controlled the students' prior knowledge, the learning achievement of Natural Sciences of the group, which is given essay test formative assessment is difference than the achievement of those with multiple choice test, (2) having controlled the students' prior knowledge, the learning achievement of Natural Sciences of the group which is given essay test formative assessment is higher than the group in multiple choice tes.